Job satisfaction among expatriate academics at China’s offshore campuses: Post-COVID challenges and cross-cultural dynamics - Duffy, Liam P. (Journal of International Students, 2026)
This qualitative study examines job satisfaction among 33 expatriate faculty members teaching Chinese international students at China’s offshore campuses. Through thematic analysis of semistructured interviews and institutional documents framed by Herzberg’s two-factor theory, this research explores the effects of cultural adaptation, faculty‒student interactions, and post-COVID-19 institutional dynamics on faculty well-being. The findings revealed that long-term emotional bonds with students were the strongest motivators. In contrast, language barriers, perceived student passivity, and subtle grade-related pressures from influential families acted as powerful hygiene stressors. An “autonomy-support paradox” was evident: institutional support (e.g., language courses, mentorship) coexisted with centralized governance that restricted academic freedom, thereby intensifying dissatisfaction. Post-COVID-19 virtual/hybrid teaching further amplified intercultural miscommunication and disengagement. Unlike prior work focused on general faculty satisfaction, this study addresses underexplored gaps in non-Western transnational education, offering practical strategies to increase expatriate retention and enrich the learning environment for Chinese international students on offshore campuses.